2017
DOI: 10.1002/1878-0261.12052
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐wide siRNA screen for regulators of tumor suppressor p53 activity in human non‐small cell lung cancer cells identifies components of the RNA splicing machinery as targets for anticancer treatment

Abstract: Reinstating wild‐type tumor suppressor p53 activity could be a valuable option for the treatment of cancer. To contribute to development of new treatment options for non‐small cell lung cancer (NSCLC), we performed genome‐wide siRNA screens for determinants of p53 activity in NSCLC cells. We identified many genes not previously known to be involved in regulating p53 activity. Silencing p53 pathway inhibitor genes was associated with loss of cell viability. The largest functional gene cluster influencing p53 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 53 publications
3
56
0
Order By: Relevance
“…However, as both are part of mitochondrial respiratory complex IV, it is possible that the complex IV inhibitors ADDA 5 [30] and tetrathiomolybdate [31] could prove useful to phenocopy any metabolic effects associated with low gene expression, promoting enhanced survival in HPV+ HNSCC. It is also important to note that COX16 is an inhibitor of p53 activity, which means that non-mitochondrial functions of COX16 should not be discounted [32]. E6 has been shown to inhibit expression of COX16 [33], which may contribute to the lower levels observed in HPV+ versus HPV-HNSCC ( Figure 3D).…”
Section: Discussionmentioning
confidence: 99%
“…However, as both are part of mitochondrial respiratory complex IV, it is possible that the complex IV inhibitors ADDA 5 [30] and tetrathiomolybdate [31] could prove useful to phenocopy any metabolic effects associated with low gene expression, promoting enhanced survival in HPV+ HNSCC. It is also important to note that COX16 is an inhibitor of p53 activity, which means that non-mitochondrial functions of COX16 should not be discounted [32]. E6 has been shown to inhibit expression of COX16 [33], which may contribute to the lower levels observed in HPV+ versus HPV-HNSCC ( Figure 3D).…”
Section: Discussionmentioning
confidence: 99%
“…Contribution of p53 and its downstream signaling events, such as plasminogen activator signaling, to the maximal common subgraph of TSHZ3 and SETD2 networks offers further support to the hypothesis that TSHZ3's role in lung adenocarcinoma include regulation of p53 activity [44]. Overall, comparing and contrasting of dysregulated signaling networks of different mutations offered us a unique look into the intricate molecular changes tumors rely on to survive.…”
Section: Discussionmentioning
confidence: 69%
“…revealed a relationship between SETD2 and p53 [45], in which SETD2 can contribute to the regulation of p53 signaling by enhancing its transcriptional activities. Additionally, a recent study discovered a connection between TSHZ3 and p53, where TSHZ3 is identified as an inhibitor of p53 activity in lung cancer cell lines [44]. Another major contributor to this maximal common subgraph is "Urokinasetype plasminogen activator (uPA) and uPAR-mediated signaling", highlighted in purple in Figure 4c.…”
Section: Network Of Mutations Observed In Lung Adenocarcinomamentioning
confidence: 92%
See 1 more Smart Citation
“…Mlinc.28428.2 is down-regulated when JPX, SERTAD4-AS1, BOLA3-AS1, and SNRPD3 are KD, and over-expressed with the KD of PTCHD3P1, ERVK3.1, MEG3, among other lncRNAs without reported function ( Figure 5A). Interestingly, interactions between p53 pathway and JPX [51], SNRPD3 [52] and MEG3 [53,54]) respectively, have been previously reported. All these features converge on the hypothesis of a link between the function of Mlinc.28428, stress response, senescence and cellular maintenance.…”
Section: In Silico Prediction Of Lncrnas Interactions and Functionsmentioning
confidence: 82%